Predictors of literacy skills among Chinese preschoolers - Chan, Mei Yee; Arshat, Zarinah; Baharudin, Rozumah (Photonics, 2013)
This study was designed to determine the predictors of literacy skills among Chinese preschoolers. There were 136 preschoolers aged ranged between three to six years old with their parents and teachers recruited in this study using a Multi-Stage Cluster sampling technique. Home-based learning activities were measured using Home Learning Environment Questionnaire (Lonigan & Farver, 2002). Meanwhile, children’s literacy skills were respectively assessed using Test of Early Reading Ability Third Edition (Reid, Hresko, & Hammill, 2001). This study found that preschoolers with higher level of literacy skills were came from families who practiced more home-based learning activities, and have highly educated parents and high family monthly income. Besides that, findings revealed that older children perform high level of literacy skills. The findings of this study imply that home learning was the most significant unique predictor of child’s literacy skills within all tested variables.